Addressing Veterinary Care Gaps for Tiny Dairy Enterprises in India: An In-Depth Analysis - R Kavitha, Ramakant Upadhyay, Zeeshan Ahmad Lone (Revista Electronica de Veterinaria, 2024)
The livelihoods of small-scale dairy farmers in India depend on the health and productivity of their animals, which can be ensured by filling the gaps in veterinary care for microdairy operations. This study focuses on the numerous challenges that dairy producers in various Indian states confront. The main characteristic of the eastern states is their unfavorable climate. The northeastern region is mostly hilly, and the main problems faced by dairy producers were worries about the low price of milk, the lack of green fodder, repeat breeding, and insufficient treatment facilities. The largest state in India is the Central States, where dairy producers deal with issues like low milk prices, inferior animals, underproductive local cows, and subpar feed and fodder. Similar issues with time veterinary services, inadequate disease expertise, and inadequate irrigation infrastructure existed in the western states. The main issues Southern states faced were the high cost of labor and veterinary care, the high cost of dairy products, feed, and concentrate, and the low incidence of artificial intelligence conception.